Pengaruh Kualitas Produk, Citra Merek dan Celebrity Endorser terhadap Keputusan Pembelian Melalui Minat Beli Pakaian Bekas sebagai Variabel Intervening”: Studi Kasus Konsumen di Kota Surabaya - Niluh Nyiman Puspita; Rusdi Hidayat Nugroho (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Humans are social creatures who help each other. Fundamentally, human needs consist of clothing, food and shelter. Human life is often fickle. Communities are required to keep abreast of existing developments. Apart from human needs that can change a person, namely lifestyle. In Indonesia selling used clothes has become a livelihood. Clothing consumption in Indonesia in 2014 reached IDR 154.3 trillion. The population in this study are people who live in Surabaya. The number of samples used in this study were 96 respondents and for representative results, the researchers took 100 respondents. The results of this study are product quality (X1), brand image (X2), celebrity endorsers (X3) influence purchasing decisions (Y). Product Quality (X1), Brand Image (X2), Celebrity Endorser (X3) influence the purchase decision (Y) through Purchase Intention (Y). Keywords: Marketing Strategy, Product quality, brand image, celebrity endorser